Delineating floodplain and upland areas for hydrologic models: a comparison of methods. Issue 23 (2nd August 2016) - Rathjens, H.; Bieger, K.; Chaubey, I.; Arnold, J. G.; Allen, P. M.; Srinivasan, R.; Bosch, D. D.; Volk, M.
Abstract: A spatially distributed representation of basin hydrology and transport processes in hydrologic models facilitates the identification of critical source areas and the placement of management and conservation measures. Floodplains are critical landscape features that differ from neighbouring uplands in terms of their hydrological processes and functions. Accordingly, an important step in watershed modelling is the representation of floodplain and upland areas within a watershed. The aim of this study is (1) to evaluate four floodplain–upland delineation methods that use readily available topographic data (topographic wetness index, slope position, uniform flood stage, and variable flood stage) with regard to their suitability for hydrological models and (2) to introduce an evaluation scheme for the delineated landscape units. The methods are tested in three U.S. watersheds ranging in size from 334 to 629 km 2 with different climatic, hydrological, and geomorphological characteristics. Evaluation of the landscape delineation methods includes visual comparisons, error matrices (i.e. cross‐tabulations of delineated vs reference data), and geometric accuracy metrics. Reference data were obtained from the Soil Survey Geographic (SSURGO) database and Federal Emergency Management Agency (FEMA) flood maps. Results suggest that the slope position and the variable flood stage method work very well in all three watersheds. Overall percentages of floodplain and upland areas allocated correctly were obtained by comparing delineated and reference data. Values range from 83 to 93% for the slope position and from 80 to 95% for the variable flood stage method. Future studies will incorporate these two floodplain–upland delineation methods into the subwatershed‐based hydrologic model Soil and Water Assessment Tool (SWAT) to improve the representation of hydrological processes within floodplain and upland areas. Copyright © 2016 John Wiley & Sons, Ltd.